2010
DOI: 10.1007/s10072-010-0431-1
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment with a novel aquaporin 4 inhibitor, TGN-020, significantly reduces ischemic cerebral edema

Abstract: We investigated the in vivo effects of a novel aquaporin 4 (AQP4) inhibitor 2-(nicotinamide)-1,3,4-thiadiazole, TGN-020, in a mouse model of focal cerebral ischemia using 7.0-T magnetic resonance imaging (MRI). Pretreatment with TGN-020 significantly reduced brain edema associated with brain ischemia, as reflected by percentage of brain swelling volume (%BSV), 12.1 ± 6.3% in the treated group, compared to (20.8 ± 5.9%) in the control group (p < 0.05), and in the size of cortical infarction as reflected by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
107
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(112 citation statements)
references
References 19 publications
5
107
0
Order By: Relevance
“…The role of AQPs in brain water balance received much attention recently (32). AQPs are membrane proteins responsible for cellular water permeability.…”
Section: Discussionmentioning
confidence: 99%
“…The role of AQPs in brain water balance received much attention recently (32). AQPs are membrane proteins responsible for cellular water permeability.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibitors of AQP-4 and MMP-9 may protect the BBB to a certain extent (20). The extent of brain edema observed in cerebral ischemia/reperfusion animals was significantly reduced following inhibition, and the animals demonstrated an improved prognosis (21)(22)(23). These results indicated that the mechanism underlying BBB protection may be associated with the inhibition of AQP-4 and MMP-9 function.…”
Section: Discussionmentioning
confidence: 84%
“…This group further identified a novel aquaporin-4 inhibitor called 2-(nicotinamide)-1,3,4-thiadiazole (TGN-020). In a brain ischemic model, they found significant reductions in the cerebral edema and cortical infarction size in the pretreated mice [54]. …”
Section: Aquaporin-4 As a Therapeutic Target In Cerebral Edemamentioning
confidence: 99%